PENINGKATAN KESELAMATAN LALU LINTAS DIRUAS JALAN PETAPAHAN – SURAM KM ± 59-60 DESA PETAPAHAN KABUPATEN KAMPAR - Husni Mubarak; Desky Aldino; Puspa Ningrum (Racic : Rab Construction Research, 2023)
Petapahan – Suram KM ±59 - 60 is a causeway with the status of a Provincial Road which is the authority of the Riau Provincial Transportation Office in completing the infrastructure aspects of the Petapahan - Suram KM ±59 - 60 road section. With such conditions, traffic problems arise in the form of traffic accidents. Therefore, to overcome the traffic problem, an analysis is needed to overcome the problem. The analysis method used in this peelitian is by Macro Analysis and Micro Analysis. Macro Analysis was conducted to determine the characteristics of accidents in general how the tendency of traffic accidents on the Petapahan – Suram KM ±59 - 60 road section. Macro Analysis uses simple numerical analysis namely analysis of the time of the accident incident, analysis based on the month of the incident, analysis of accident victims, analysis of the type of accident. For micro analysis consists of several analyses consisting of analysis based on accident chronology data, analysis of factors causing accidents, analysis of instantaneous. speed / spot speed and analysis of stop visibility. After the analysis, it was concluded that the factors causing many accidents that occurred in Petapahan – Suram KM ±59 - 60 were human factors and environmental factors. The human factor is the main factor in accidents that occur. So this research is needed to overcome these problems such as addition, replacement and maintenance for road equipment facilities in accordance with technical requirements.